2013
DOI: 10.1016/j.actpsy.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Body image distortions in healthy adults

Abstract: Distortions of body image have often been investigated in clinical disorders. Much of this literature implicitly assumes healthy adults maintain an accurate body image. We recently developed a novel, implicit, and quantitative measure of body image - the Body Image Task (BIT). Here, we report a large-scale analysis of performance on this task by healthy adults. In both an in-person and an online version of the BIT, participants were presented with an image of a head as an anchoring stimulus on a computer scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 41 publications
11
91
2
2
Order By: Relevance
“…Analogous distortions have also been found on tasks in which representations of body size and shape are inferred from the pattern of proprioceptive localization judgments, both for the hand (Longo & Haggard, 2010 and torso (Hach & Schütz-Bosbach, 2010). Fuentes and colleagues have also found similar biases using a 'body Bilateral Tactile Anisotropy 18 image task' in which participants judge the relative location of body landmarks by clicking the corresponding place on a monitor, both for the body as a whole (Fuentes, Longo, & Haggard, 2013a;Fuentes et al, 2013b) and the face specifically (Fuentes et al, 2013c). The finding of qualitatively similar distortions on widely disparate skin surfaces and across tasks raises the possibility that a general bias to represent the body as squatter and fatter than it is may reflect a basic principle of body representation.…”
Section: Discussionmentioning
confidence: 83%
“…Analogous distortions have also been found on tasks in which representations of body size and shape are inferred from the pattern of proprioceptive localization judgments, both for the hand (Longo & Haggard, 2010 and torso (Hach & Schütz-Bosbach, 2010). Fuentes and colleagues have also found similar biases using a 'body Bilateral Tactile Anisotropy 18 image task' in which participants judge the relative location of body landmarks by clicking the corresponding place on a monitor, both for the body as a whole (Fuentes, Longo, & Haggard, 2013a;Fuentes et al, 2013b) and the face specifically (Fuentes et al, 2013c). The finding of qualitatively similar distortions on widely disparate skin surfaces and across tasks raises the possibility that a general bias to represent the body as squatter and fatter than it is may reflect a basic principle of body representation.…”
Section: Discussionmentioning
confidence: 83%
“…The full experiment included the IAT, the explicit questions targeting body preference, some groupspecific questions and the Body Image Task (Fuentes et al, 2013a(Fuentes et al, , 2013b. The latter is not reported here, as the number of participants was too low (only 14 individuals with xenomelia completed the task) and an analysis of the data would not have allowed any reasonable interpretation.…”
Section: General Proceduresmentioning
confidence: 99%
“…Hashimoto and Iriki [2013] used distorted photographs of participants' own bodies to show that women estimate photographs distorted by 10% in width to be photographs of their current body size, but photographs distorted by 30% in width were estimated to belong to others. Other work finds that healthy individuals show large distortions in size and shape of their hand [Longo and Haggard 2012a] as well as their body [Fuentes et al 2013], suggesting that people perceive both their hand and body to be wider and shorter compared to their actual size. Mischner et al [2013] showed that exposure to music videos can bias both the perceived and the ideal body size of healthy women.…”
Section: Introductionmentioning
confidence: 99%